Iron, Copper And Tin Incorporated Rice Husk Ash Silica: Preparation, Characterization And Application As Catalysts For Friedel-Crafts Benzoylation Reactions - Hassan, Ishraga Abdelmoniem (2011)

(untitled)
Iron, copper and tin incorporated silica catalysts were prepared via sol-gel method using the silica extracted from rice husk ash. The modified catalysts were denoted as RHA-xFe (x = 5, 10, 15 and 20 wt.%), RHA-10Cu and RHA-10Sn. Prepared catalysts were characterized by various physico-chemical techniques such as XRD, FT-IR, N2-sorption, AAS, SEM-EDX, TEM, DR UV/Vis, solid state 29Si MAS NMR, EPR, TGA-FT-IR and FT-IR-pyridine adsorption. The catalysts were found to be amorphous. Elemental analysis confirmed the presence of the metals in the silica framework.